'My heart was already cooked': girl soldiers and situated moral agencies. Issue 2 (4th March 2018) - Vaha, Milla Emilia; Vastapuu, Leena
Abstract: The number of studies on children in war has steadily increased in the fields of international relations, international law and moral philosophy in recent years. Most of this research has evolved around the legal and moral status of children in war. The status of girl soldiers is particularly intriguing, as it conflates common assumptions about both women and children as innocent victims of war. In this paper we look at narratives of children's victimhood in the context of war by concentrating on girls who participated, in various forms, in the two Liberian civil wars from 1989 to 1997 and 2000 to 2003. Drawing on interviews conducted with women war veterans, we make the case that the study of child soldiers in general—and girl soldiers in particular—would benefit from a more contextually sensitive and empirically informed study of girls' experiences, specifically regarding the possibilities and limitations of their capacity to be agents of war. We demonstrate how the agential capacities of children are case sensitive and argue that scholarship must better take into account the complex contextuality of childhood and agency in the study of children in war.